Mobile Applications to Promote Mental Health among Breast Cancer Patients: A Rapid Review: Mobile Apps to promote mental health - BorjAlilu, Somayyeh; Karbakhsh, Mojgan; Lotfi, Mehrnoush; Haghshenas, Elham; Kaviani, Ahmad (Archives of Breast Cancer, 2023)
Background: The use of mobile services for health promotion is rapidly increasing. The purpose of this paper is to review studies using cell phone applications as an intervention to improve mental health in breast cancer patients and to provide an overview of their effectiveness. Methods: A systematic search in PubMed, Scopus, Web of Science and PsycINFO was performed to retrieve relevant studies published from 2010 to 2020. The criteria for inclusion were included in any study illustrated about the breast cancer, English papers and mental health. Related articles were selected based on inclusion and exclusion criteria. The survey and meta-synthesis of included articles were conducted based on predefined classification.then From the selected studies, the following information was extracted: authors, publication date, study objectives, study population, study design, interventions, and results. Results: 81 papers were retrieved with databases and 46 articles were reviewed. At the end, 7 articles were selected for analysis. We identified 7 RCT studies that utilized a mental health application as a mental health intervention in breast cancer patients. The results showed all of studies effectiveness of the mobile apps on the stress, depression, anxiety, self-efficacy, social support, resiliency and coping with breast cancer. Conclusion: This study demonstrates the important role of mobile apps in promoting mental wellness of breast cancer patients. Mobile app interventions can be implemented to decrease depression through positive impacts on stress management, self-efficacy, resilience and breast cancer adaptation. We recommend that the role of mobile apps for the prevention and rehabilitation of mental health aspects in breast cancer patients would be examined through a blended delivery management approach in future studies.